FINANCIAL LITERACY AND INCLUSION TOWARDS MSME’S PERFORMANCE IN CIWIDEY SUB-DISTRICT - Nugraha, Nura; Rusliati, Ellen; Alghifari, Erik Syawal (AMAR (Andalas Management Review), 2023)
Purpose: This study aims to find out the influence of financial literacy and inclusion towards MSME’s financial performance in Ciwidey Sub-district. Methods: Methods used in this study are descriptive and verification with the number of samples as much as 60 respondents. Analysis data: The test on research instrument uses validity and reliability test, while technique on data analysis uses multiple linier regression, double correlation and coefficient of determination. The test result showed that the entire statements written in the questionnaire were valid and reliable. Results and discussion: The result of verification analysis showed that simultaneously, financial literacy and inclusion give positive and significant impacts to MSME’s financial performance as much as 66.9%, while partially, financial literacy gives positive and significant impact as much as 48.50% and financial inclusion as much as 18.40% on financial performance. Conclusion: The level of financial literacy, financial inclusion, and MSME’s financial performance on MSME’s businessmen in Ciwidey Sub-district were on the category of deficient; since there were a lot of indicators which were below average score and needed to be improved. Financial literacy had more positive significant effect on MSME’s financial performance than financial inclusion.